Are Non-reef Habitats as Important to Benthic Diversity and Composition as Coral Reef and Rubble Habitats in Submarine Canyons? Analysis of Controls on Benthic Megafauna Distribution in the Porcupine Bank Canyon, NE Atlantic - Appah, J. K. M.; Lim, A.; Harris, K.; O’Riordan, R.; O’Reilly, L.; Wheeler, A. J. (Frontiers in Marine Science, 2020)
Submarine canyons support high biomass communities as they act as conduits where sediments, nutrients, and organic matter from continental shelves, or those that are carried along by slope currents, are transported into the abyssal zone. The Porcupine Bank Canyon (PBC), located on the Irish continental margin and isolated from terrigenous inputs, reveals a complex terrain and substrate variation that affect the distribution of benthic fauna. Here, ROV-based benthic video, conductivity-temperature-depth (CTD), current velocity profiles, suspended particulate organic matter (POM) and bathymetric data were assessed to determine the controls on the distribution of benthic megafauna throughout the canyon. Multivariate analysis of the benthic community reveals significant differences in community structure among habitats and site locations throughout the canyon. Furthermore, these results show that non-reef habitats exhibit more variation in the composition of benthic taxa than coral reef and rubble habitats, with the following species contributing most to the structural differentiation between habitats: Leiopathes glaberrima (12.46%), Hexadella dedritifera (10.37%), Cidaris cidaris (9.31%), Aphrocallistes beatrix (9.33%), Araeosoma fenestratum (9.11%), Stichopathes cf. abyssicola (7.39%), Anthomastus grandiflorus (4.66%), and Benthogone rosea (3.84%). In addition, greater diversity, taxa evenness and high abundance of motile fauna were observed in non-reef habitat and the canyon flank. Seabed terrain features (depth, slope) are the most important environmental drivers that affect benthic taxa distribution while site locations and habitat type are the categorical variables that influence taxa distribution in the PBC. The highest mean current speed was observed on the canyon flank where the highest Shannon’s diversity was recorded while mean current speed ranged from 18.2–31.3 cm s–1. As the PBC is cut off from direct terrigenous input, this research contributes to understanding cold-water coral habitat responses to natural Northeast Atlantic environmental conditions. The findings of the current study will inform key stakeholders on how to responsibly interact with the canyon benthic habitats and can help inform policy makers on the effective conservation and management of the cold-water coral habitat in the PBC and other canyons.